Peran Asuransi Syariah terhadap Penguatan Pertumbuhan Ekonomi - Maisaroh, Neng; Hilal, Syamsul; Asriani, Asriani (CV. Creative Tugu Pena, 2024)
The aim of article analyzing the role of sharia insurance in strengthening economic growth. Analyzing the role of sharia insurance in strengthening economic growth is the goal of this study. This study uses a qualitative type of research. The approach used by the researcher is a literature study approach model. Data collection uses literature studies such as books, scientific journals, and written reports related to sharia insurance and economic growth. The results of this study show that Sharia Insurance plays an important role in strengthening economic growth. Sharia insurance plays an important role in increasing investment, improving the community's economy, as a source of financing for development, and can divert financial risks caused by unexpected events or disasters. Keywords: Sharia Insurance, Economic Growth, Sharia Economics